The type and abundance of clown fish (amphiprion sp.) In conservation areas of kasiak island of pariaman city of west sumatera - Ryan Mustakim; Thamrin '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was done in June 2014 in the concervation area of Kasiak Island, Pariaman City, West Sumatera. The aim of study was to observe the species composition and its abundance of clown fish ( Amphiprion sp. ). The method used was quadrant transect. The data was analysed by t-test for among stations.The study resulted that 2 species of clown fish,i.e. Amphiprion akallopisos and A. ocellaris, were recorded. The abundance for each station categorized as low, withe the value ranged from 0.03 ind/m2 – 0.24 ind/m2. The most abundant fish found was A. akallopisos,i.e. 18 individuals at station I. The diversity index ranged 0.764 – 0.811, the dominance index ranged 0.115 – 0.405, whereas the eveness index ranged 0.625 – 0.654. The study in general, did not see the difference in fish abundance among the station.Keywords: Type, Abundance, Clown Fish, Kasiak Island, West Sumatera